Manusia dan Geguritan di Surabaya (Kajian Semiotik Disertai Telaah Subkultur) - Joko Susilo; Niko Fediyanto (Jurnal Sosial Humaniora, 2025)
The movement of geguritan (javanese poem) is not just a resistance movement towards the general rule of Javanese literature. It provides convenience for the community (in the same subculture) to understand Javanese culture easier. This movement refers to the 'whole way of life' or 'maps of meaning' that makes this world understandable by its members. The word 'sub' connotes a specific, unique condition and different than the dominant society. Person who was born in arekan environment or Suroboyoan often encounter difficulties when trying to comprehend Mataraman Javanese. Geguritan is a manifestation of the ideas or creativity generated by penggurit (poet). In Surabaya, a group of geguritan authors is one subculture, that offers a new view, reinterpret the old view, and sometimes even break a single truth that have been taught long enough to Javanese community in Surabaya.